"Gave me a line of ice and I got hooked": Exploring narratives of initiating methamphetamine use. Issue 1 (18th December 2018) - Schmidt, Michael; Dillon, Patrick J.; Jackson, Bianca M.; Pirkey, Paige; Kedia, Satish K.
Abstract: Objective: This study explores factors associated with methamphetamine initiation based on the narratives from an online support group for methamphetamine users. Methods: We conducted a qualitative study of 202 first‐person narratives submitted to an anonymous, online support group for methamphetamine users. The narratives were analyzed in the Dedoose qualitative software using Charmaz's adaptations to Glaserian grounded theory methodology. Results: Ten factors for initiating methamphetamine use emerged from our analysis and corresponded to three constructs from the Theory of Planned Behavior: attitude (needing energy to work, wishing to escape pain, wanting to have fun, and desiring a thinner body), subjective norms (ubiquity of methamphetamine use, yearning for closer relationships, and wanting to fit in), and perceived behavioral control (believing addiction is inevitable, feeling forced to fit in, and having no real control). Many participants described initiating methamphetamine use because they believed it would help them meet personal goals or needs. Other participants began using it out of curiosity, to develop relationships, and/or because of the drug's ubiquity in their social environments. Some users described how their perceived lack of control left them with limited ability to resist trying the drug. Conclusions: Results from this study may aid public health researchers and interventionists seeking theoretically informed methamphetamine prevention programs.